TA Treatment of Depression - A Hermeneutic Single-Case Efficacy Design Study - „Peter‟ - Mark Widdowson (International Journal of Transactional Analysis Research, 2012)
Hermeneutic Single-Case Efficacy Design (HSCED) is a systematic case study research method involving the cross-examination of mixed method data to generate both plausible arguments that the client changed due to therapy and alternative explanations. The present study uses HSCED to investigate the outcome of short-term TA psychotherapy with a young man with severe depression. The objective of the research was to investigate the effectiveness of short-term TA therapy for the treatment of depression and to explore and identify key aspects of the TA therapy process and associated factors promoting change amongst effective cases. To enhance rigour and to address potential for researcher allegiance, independent psychotherapy researchers have adjudicated the case and offer a verdict on outcome. The conclusion of the adjudicators is that the client changed considerably-substantially, and that these changes were substantially due to the effect of therapy.